RESPONS PERTUMBUHAN BIBIT AREN ( Arenga pinnata Me - Manahan Manahan; Lollie Agustina P. Putri; Yusuf Husni (Jurnal Agroekoteknologi, 2014)
ABSTRACTOne of the problems encountered in the development of the sugar palm seedling there is no fertilizer issuitable for palm nursery. Based on this, the objective of this research was to determine the effect of liquidorganic fertilizer on the growth of sugar palm seedling. The research was conducted at area University ofSumatra Utara, Medan with ± 25 m height above sea level which is held in August to December 2012randomized block design was used. The treatment was a liquid organic fertilizer with some types anddossages of different fertilizers. The treatment was used four replication. The type and dosage of fertilizerwas used in control (without organic liquid fertilizer), organic liquid fertilizer N: <2%, P2O5: <2%, K2O:<2% (50 cc / seeds), organic liquid fertilizer N: <2%, P2O5: <2%, K2O: <2% (75 cc / seeds), organic liquidfertilizer P2O5: <2%, K2O: <2% (4.5 cc / seeds), organic liquid fertilizer P2O5: <2 %, K2O: <2%(7cc/bibit), liquid organic fertilizer N 0.011%, P 6.26 mg/100 ml, 72.13 K mg/100ml, auxin IAA 0.066 g / l,GA3 gibberellins 0.093 g / l (6cc/bibit), liquid organic fertilizer N 0.011%, P 6.26 mg/100 ml, 72.13 Kmg/100ml, auxin IAA 0.066 g / l, GA3 gibberellins 0.093 g / l (8.5 cc / seeds). Parameters measured werepalnt height, leaves number, stem diameter, total leaves area, shoot weight, root weight, shoot dry weight androot dry weight. The results showed that the liquid organic fertilizer had not been significantly affected forall parameters were palnt height, leaves number, stem diameter, total leaves area, shoot weight, root weight,shoot dry weight and root dry weight.Keywords: iquid organic fertilizer, palm